Self-Management Untuk Meningkatkan Kedisiplinan Belajar Siswa: Studi Kasus di SMA Negeri 5 Banda Aceh - Fajriani Fajriani; Nur Janah; Desi Loviana (Jurnal Pencerahan, 2016)
Discipline is one of the important aspects of an individual's life. This study aims was to examine and analyze the level of learning the discipline of the student in SMAN 5 Banda Aceh before and after groups counseling service using self-management techniques and to determine whether there is a significant increase learning discipline between before and after self-management techniques. The quantitative approach with the pre-experiment, one group pre-post test design was performed in this study. Samples were taken by purposive sampling as much as 10 students of the 30 students that suspected of having a low level of learning discipline. The collecting data were used a learning discipline questionnaires by using Likert Scale 1-4. Data were analyzed by non-parametric statistical test (Sign test). The results showed that the level of the student's learning discipline was increased after given self-management techniques as many as 10 treatments, with a mean pre-post test 150.7 147.5 i.e. from the low category to a higher category, with a positive change. Based on binomial table where n= 10 and p 0.05, the probability of X 10 is 0.001. It is concluded that the self-management techniques can improve studentsâ€™ learning discipline.Â